In pursuit of a foundational accountancy philosophy - Buys, P. (Koers, 2008)
Recent accounting history is characterised by many developments, including several high-profile corporate failures, such as Enron, Parmalat and even Saambou, as well as major developments in financial reporting standards, such as the broadbased acceptance of international financial reporting standards and the convergence efforts between the UK-based International Accounting Standards Board and the US-based Financial Accounting Standards Board. As a result, long-accepted accounting assumptions are being challenged in favour of new principles and practices. Furthermore, in academic circles the scientific foundation of accounting is being questioned. At many universities, limited education is taking place in the underlying theory and philosophy of accounting in favour of teaching prospective accountants how to pass difficult professional exams. Seen against this backdrop, a reconsideration of the objectives and purpose of accountancy may be overdue. This article attempts to illuminate the intrinsic assumptions and objectives of accountancy, seen in the light of modern-day accounting issues and developments.